The Need, Function, and Theory of Elementary Counseling - Altmann, H.A. (Canadian Journal of Counselling and Psychotherapy, 2012)
A review of the literature on elementary counseling was made in an attempt to determine the status of this  field. Specific issues involving need, function, and theory of elementary counseling were discussed.